Universal Access in Human-Computer Interaction. Access to Interaction : 9th International Conference, UAHCI 2015, Held as Part of HCI International 2015, Los Angeles, CA, USA, August 2-7, 2015, Proceedings, Part II - Antona, Margherita; Stephanidis, Constantine; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
The four LNCS volume set 9175-9178 constitutes the refereed proceedings of the 9th International Conference on Learning and Collaboration Technologies, UAHCI 2015, held as part of the 17th International Conference on Human-Computer Interaction, HCII 2015, in Los Angeles, CA, USA in August 2015, jointly with 15 other thematically similar conferences. The total of 1462 papers and 246 posters presented at the HCII 2015 conferences were carefully reviewed and selected from 4843 submissions. These papers of the four volume set address the following major topics: LNCS 9175, Universal Access in Human-Computer Interaction: Access to today's technologies (Part I), addressing the following major topics: LNCS 9175: Design and evaluation methods and tools for universal access, universal access to the web, universal access to mobile interaction, universal access to information, communication and media. LNCS 9176: Gesture-based interaction, touch-based and haptic Interaction, visual and multisensory experience, sign language technologies, and smart and assistive environments LNCS 9177: Universal Access to Education, universal access to health applications and services, games for learning and therapy, and cognitive disabilities and cognitive support and LNCS 9178: Universal access to culture, orientation, navigation and driving, accessible security and voting, universal access to the built environment, and ergonomics and universal access.
Gesture-based interaction -- Touch-based and Haptic Interaction -- Visual and multisensory experience -- Sign language technologies -- Smart and assistive environments.
Keywords: Computer science; Information storage and retrieva; User Interfaces and Human Computer Interaction; Computers and Society; Information Storage and Retrieval; Information Systems Applications (incl. Internet).